Improvement of the sensitivity of circulating tumor DNA-based liquid biopsy: current approaches and future perspectives - Ekaterina S. Kuligina; Grigoriy A. Yanus; Evgeny N. Imyanitov (Exploration of Targeted Anti-tumor Therapy)
Liquid biopsy (LB) is a complex of procedures aimed at the detection of tumor-derived fragments (nucleic acids, proteins, cells, etc.) persisting in the blood or other body fluids. It can be utilized for early cancer diagnosis, analysis of biomarkers of tumor drug sensitivity and prognosis, monitoring of minimal residual disease (MRD), etc. Circulating tumor DNA (ctDNA) is an accessible and reliable LB analyte as it may contain tumor-specific mutations and is amenable to efficient detection by next-generation sequencing (NGS) or droplet digital PCR (ddPCR). High level of ctDNA is typically associated with increased tumor burden and poor prognosis, whereas treatment-related ctDNA clearance increases the probability of a favorable disease outcome. Major efforts have been invested in enhancing the analytical performance of ctDNA detection. Stimulation of apoptosis of tumor cells by irradiation of cancer lumps has been shown to result in a transient but modest increase in ctDNA concentration. There are several sophisticated modifications of ultra-deep NGS protocols, which discriminate between “true” low-copy mutation-specific signals and sequencing artifacts. Slowing physiological ctDNA decay by interfering with liver macrophages and circulating nucleases has shown promise in animal experiments. Reproducibility of ctDNA-based LB assays remains insufficient for samples with ultra-low content of ctDNA; hence, interlaboratory harmonization of ctDNA testing procedures is of paramount importance.